Microshear Bond Strength of Self-etching Bonding Systems to Ultrasound Diamond Bur-prepared Dentin - Borges, Alessandra Buhler [UNESP]; da Silva, Melissa Aline [UNESP]; Souto Borges, Alexandre Luiz [UNESP]; Werkman, Cristina [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Pucci, Cesar Rogerio [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: The aim of this study was to evaluate the influence of dentin abrasion on the microshear bond strength of two self-etching adhesive systems, using either an ultrasound diamond bur or a high-speed diamond bur.Materials and Methods: Twenty noncarious human third molars were sectioned mesiodistally into halves. The enamel was ground to expose a flat dentin surface on both sections. The dentinal surfaces were randomly assigned to two groups, depending on the method of smear layer preparation: ultrasound diamond bur (UB) or conventional diamond bur (CB). The prepared dentin surfaces received one of two self-etching systems: Clearfil SE Bond (CF) and One-Up Bond F (OB). A composite cylinder with a 0.95-mm diameter was bonded to each specimen and the microshear bond test was performed. The results were expressed in MPa and were subjected to two-way analysis of variance (ANOVA) and Tukey's test (alpha = 0.05).Results: There was no significant difference in dentin bond strength when comparing the conventional and ultrasonic abrasion methods. When the adhesive systems were compared, Clearfil SE Bond achieved higher bond strength means than did One-Up Bond F.Conclusion: The dentin surface preparation method did not influence the microshear bond strength and the Clearfil SE Bond adhesive system, independent of bur type used, Clearfil SE Bond showed higher bond strengths than did the One-Up Bond F adhesive system.
Keywords: microshear bond strength; self-etching adhesive systems; ultrasound; diamond bur